Vein Pattern Recognition: A secured way of Authentication (International Journal of Engineering and Computer Science, 2016)
In today’s world the technology is growing and improving day by day and hence the chance of threat to personal information as well as nationalized data is also increasing. No doubt there are a lot of methods which developed either from inside or outside to secure the information but those methods didn’t produce satisfactory results so we need a technology that secure our information more efficiently from an unauthorized access. For the purpose Palm vein authentication is the newest biometric technique with high level of accuracy came into existence and becoming popular these days. In this technique the vascular patterns of an individual’s palm used as personal identification data. This technique can be used in various fields like ATM, hospitals, for Attendance records, driver identification, on construction sites, banking and financial institutions etc. Business growth can also be achieved by reducing the size of the palm vein sensor and shortening the authentication time. This paper presents a review on the palm vein technology and its development, working principle, its applications, and advantages of using this technology.